The relevance of oncogenes as prognostic markers in cervical cancer. Issue 5 (1st August 2002) - Soh, L. T.; Heng, D.; Lee, I. W.; Ho, T. H.; Hui, K. M.
Abstract : To study the prevalence of the oncogenes c-myc, IFN-α; c-erbB2; H-ras codon 12, 13, and 61; c-fos; and E6/E7 oncogenes of human papillomavirus (HPV) 16 in patients with invasive carcinoma of the cervix and their prognostic significance, genomic DNA and RNA were isolated from tissues of 275 patients in Singapore with nonmetastatic cervical cancer and 32 patients with normal cervix. The levels of expression of the various oncogenes were quantified by PCR using the respective primers. When the PCR data on the DNA were analyzed by the log-rank test, IFN γ ( P = 0.02) and H-ras codon 12 and 13 ( P = 0.02) were found to be prognostic. In the multivariate analysis, a statistically significant trend for increasing risk with higher quartiles was found for c-myc ( P = 0.007) and c-erbB2 ( P = 0.03). After adjusting for age and stage, a correlation appears between the amplification of the oncogenes c-myc, c-erbB2, and H-ras codon 12, 13, and 61 and the development of recurrent cervical cancer. Further adjustment to include the parameters of treatment and histology type did not change the outcome of the correlation observed.